Health behaviors and life satisfaction in college students - Pettay, Robert Francis (Kansas State University, 2008)
This study explored the relationship between a variety of health behaviors and life satisfaction in college students. University students (N=794) enrolled in a midwestern university during the Fall, 2006 and Spring, 2007 semester, completed an online Health Behavior Assessment designed to measure body mass index (BMI), frequency of physical activity behavior, fruit and vegetable consumption, sleep behavior, alcohol use, frequency of use of stress-management skills, stage of change for physical activity, stage of change for fruit and vegetable consumption, stage of change for frequency of stress-management skills, and life satisfaction. As predicted, significant correlations were found between life satisfaction and BMI, frequency of physical activity, fruit and vegetable consumption, and frequency of use of stress- management skills. Students who regularly received 6-8 hours of sleep showed higher levels of life satisfaction. Students in the maintenance stage of change for physical activity behavior and stress-management skill use were found to have higher levels of life satisfaction compared to individuals in earlier stages of change. Results indicated that increased life satisfaction is related to a variety of health behaviors in college students.
Keywords: life satisfaction; college student; physical activity; stress management; body mass index; Education, Physical (0523); Psychology, Cognitive (0633)